Cyanobacterial promoted enrichment of rare earth elements europium, samarium and neodymium and intracellular europium particle formation. Issue 56 (11th October 2019) - Fischer, Christian B.; Körsten, Susanne; Rösken, Liz M.; Cappel, Felix; Beresko, Christian; Ankerhold, Georg; Schönleber, Andreas; Geimer, Stefan; Ecker, Dennis; Wehner, Stefan
Abstract : Efficient biosorption and intracellular accumulation of selected rare earth elements from aqueous solutions by cyanobacteria type Anabaena . Abstract : In the recovery of rare earth elements (REE) microbial biosorption has shown its theoretical ability as an extremely economically and environmentally friendly production method in the last few years. To evaluate the ability of two cyanobacterial strains, namely Anabaena spec. and Anabaena cylindrica to enrich dissolved trivalent REE, a simple protocol was followed. The REE tested in this study include some of the most prominent representatives, such as europium (Eu), samarium (Sm) and neodymium (Nd). Within the experiments, a fast decrease of the REE 3+ concentration in solution was tracked by inductively coupled plasma mass spectrometry (ICP-MS). It revealed an almost complete (>99%) biosorption of REE 3+ within the first hour after the addition of metal salts. REE 3+ uptake by biomass was checked using laser-induced breakdown spectroscopy (LIBS) and showed that all three selected REE 3+ species were enriched in the cyanobacterial biomass and the process is assigned to a biosorption process. Although the biomass stayed alive during the experiments, up to that, a distinction whether the REE 3+ was intra- or extracellularly sorbed was not possible, since biosorption is a metabolism independent process which occurs on living as well as non-living biomass. For europium it was shown by TEM that electron dense particles, presumably europium particles with particle sizes of about 15 nm, are located inside the vegetative cyanobacterial cells. This gave clear evidence that Eu 3+ was actively sorbed by living cyanobacteria. Eu 3+ biosorption by cell wall precipitation due to interaction with extracellular polysaccharides (EPS) could therefore be excluded. Finally, with XRD analysis it was shown that the detected europium particles had an amorphous instead of a crystalline structure. Herein, we present a fast biosorptive enrichment of the rare earth elements europium, samarium and neodymium by Anabaena spec. and Anabaena cylindrica and for the first time the subsequent formation of intracellular europium particles by Anabaena spec.